Learning in adulthood : a comprehensive guide - Merriam, Sharan B., 1943-; Baumgartner, Lisa, 1964- (Jossey-Bass, 2020)
"This landmark work pulls together seminal work and current thinking on adult learning in one volume, providing a comprehensive, up-to-date overview and synthesis of what we now know about adult learning, including the context in which it takes place, who the participants are, what they learn and why, the nature of the learning process itself, major theoretical developments, and much more. Drawing from a background of work in sociology, philosophy, and critical social theory as well as psychology and education, the authors construct an inclusive perspective on adult learning, guiding readers toward new ways of thinking about teaching, learning, and the broader social implications of adult education. Comprehensive guide, complete and up-to-date. Historically the most authoritative guide in the field, with more than 80,000 copies sold life-to-date. Synthesis of latest developments in theory and research, with implications for practice. Experienced authors, leaders in the field"--